Implementation of Comprehensive Strategy and Risk at Marketing Strategy RASBiN Foundation Over Medical Bank Products - Andre Depeda Prantino; Tantri Yanuar Rahmat Syah; Dadan Ramdhani; Semerdanta Pusaka (Penerbit Kemala Indonesia, 2020)
For human resources, here the foundation takes approach 7sfrom Mckenzie which is consists of Shared Value, Strategy, Structure, Staff, Skill, System, Style. The work culture in the RASBiN foundation is addressed to a superior work culture. For the financial statements of the foundation are consists of the Laporan Relialisasi Anggaran (LRA), financial position reports, activity reports, cash flow reports, operational reports, CLAK. The collated of cash flow statement in foundation gets revenue from advertising sales, and donations from donors that are expected to take place every year with the total of amount around 10 billion for donations and annual income for pessimistic forecasting with 2% will be Rp. 9,62,333,223. Furthermore, the continued of 10 years in new foundation will be improve BEP / break even. For monthly operational expenses the foundation is Rp. 8,241,195,600 per year with an increase of 2-5% per year. In the risk analysis there are several ratios that are considered by the foundation to be fatal, one of which is technology that continues to grow and the security of user data is quite risky so the foundation strategy is to maintain and maintain consumer data storage every month and back up data with third parties.